2005
DOI: 10.2106/jbjs.d.02952
|View full text |Cite
|
Sign up to set email alerts
|

Scapulothoracic Fusion for Facioscapulohumeral Muscular Dystrophy

Abstract: In developmental dysplasia of the hip, a deficient acetabulum may be augmented by placing local autogenous iliac osseous graft, or the ilium itself, over the head of the femur with the expectation that the added bone will function as a bearing surface. We analysed this bone obtained en bloc during subsequent surgery which was performed for degenerative osteoarthritis in three patients at 6, 25 and 30 years after the initial augmentation procedure. In each patient, the augmentation comprised of red cancellous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 24 publications
1
40
1
2
Order By: Relevance
“…5 Twyman et al reported that forced vital capacity decreased by an average of 21% (range, 3.2% to 30%) in all five patients in his series who had bilateral scapulothoracic fusion. 21 Others have reported minimal or no reduction in vital capacity, respiratory volume or forced expiratory volume following scapulothoracic fusion.…”
Section: Surgical Treatmentmentioning
confidence: 84%
See 2 more Smart Citations
“…5 Twyman et al reported that forced vital capacity decreased by an average of 21% (range, 3.2% to 30%) in all five patients in his series who had bilateral scapulothoracic fusion. 21 Others have reported minimal or no reduction in vital capacity, respiratory volume or forced expiratory volume following scapulothoracic fusion.…”
Section: Surgical Treatmentmentioning
confidence: 84%
“…4 The weakness of scapular stabilisers means that the shoulder blade is abnormally mobile and rotates causing cephalad displacement and winging. 5 The increased mobility means that deltoid is also at a mechanical disadvantage and the additional effort required causes the deltoid to fatigue easily. At rest there is an elevated scapular position due to weakness of the middle and lower thirds of trapezius and internal rotation of shoulder.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with severe arm weakness may benefit from surgical fixation of the scapulae. 48,49 Immunosuppressive medications are ineffective despite the inflammatory response seen on muscle biopsies. Respiratory insufficiency occurs rarely, usually many years after disease onset.…”
Section: Facioscapulohumeral Muscular Dystrophymentioning
confidence: 99%
“… 5 9 Static winging scapula 4 in muscular dystrophy, facioscapulohumeral dystrophy, is corrected mainly by scapulothoracic fusion/arthrodesis and tendon transfer procedures. 2 , 10 – 17…”
Section: Introductionmentioning
confidence: 99%